Wavelet based approach for the investigation of vision impairments using single trial VEPs - Vijean, Vikneswaran; Hariharan, Muthusamy, Dr.; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/